Reactions of Uranyl(VI) Nitrate with Terfunctional 4-Amino Antipyrine Schiff Bases in Neutral and Alkaline pH - Abdul Samath, S.; Raman, N.; Jeyasubramanian, K.; Thambidurai, S.; Ramalingam, S.K. (Asian Journal of Chemistry, 2010)
Complexes of uranyl(VI) nitrate with the terfunctional Schiff bases, acetylaceton-4-aminoantipyrine (AcAAP), salieylal-4-aminoantipyrine (SAAP) and 2-hydroxy-1-naphthal-4-aminoantipyrine (HNAAP) of the general formulae [UO2L2](NO3]2 and [UO2L2] have been synthesised from neutral or alkaline reaction media and their spectra-structure correlation obtained. These ligands behave differently at different pH of the reaction solution. At pH 8–9 the –OH group in its deprotonated form, bonds to the metal ion along with the other two functional groups >C=O and >C=N– in an anionic terdentate manner. In neutral reaction medium (pH ca. 7) they form complexes in which the ligand systems coordinate as neutral bidentate and the –OH group involved only in hydrogen bonding with the linear [O=U=O] function.